Implementation of the SDGs under Czech Conditions and Measuring Selected Indicators - Lešáková, Petra; Baťa, Robert; Provazníková, Romana (International Business Information Management Association-IBIMA, 2017)
Sustainable development is now found as a central theme throughout the United Nations and its Agenda 2030 that introduced 17 Sustainable Development Goals that should be achieved by 2030. Nevertheless, countries have the primary responsibility to establish a national framework for achieving those Goals, but it is regional level that is essential for understanding and achieving sustainability. Therefore, the goal of this paper is to describe a process of implementation of targets of the Agenda 2030 under Czech conditions. Besides proposed procedure of indicators selection, method of decoupling is described and proposed as a tool for assessing progress in achieving Sustainable Development Goals (with emphasis on the environmental pillar) and applied on real regional data.
Implementace SDG v českých podmínkách a měření vybraných indikátorů
Keywords: Agenda 2030; Regional Development; Sustainable development; Sustainable development indicators; Agenda 2030; regionální rozvoj; udržitelný rozvoj; indikátory udržitelného rozvoje